Industry-Specific Makerspaces: Opportunities for Collaboration and Open Innovation - Zakoth, David; Mauroner, Oliver (Management international / International Management / Gestiòn Internacional, 2020)
The rise of the maker movement, including hackathons and fablabs, provides new opportunities for companies to boost innovation by collaborating with creative, tech-savvy and intrinsically motivated people, known as makers. This paper connects open innovation and maker movement research by investigating how makers and companies can work together within an industry-specific makerspace setting. We use a qualitative case study design and focus on the German photonics industry. Our results shed light on the expectations makers and companies have when considering a collaboration, along with the perceived benefits and risks. Furthermore, we uncover crucial design factors for industry-specific makerspaces.